Cloning animals by somatic cell nuclear transfer - biological factors - Enright Brian; Kubota Chikara; Tian X; Yang Xiangzhong (BMC, 2003)
Abstract Cloning by nuclear transfer using mammalian somatic cells has enormous potential application. However, somatic cloning has been inefficient in all species in which live clones have been produced. High abortion and fetal mortality rates are commonly observed. These developmental defects have been attributed to incomplete reprogramming of the somatic nuclei by the cloning process. Various strategies have been used to improve the efficiency of nuclear transfer, however, significant breakthroughs are yet to happen. In this review we will discuss studies conducted, in our laboratories and those of others, to gain a better understanding of nuclear reprogramming. Because cattle are a species widely used for nuclear transfer studies, and more laboratories have succeeded in cloning cattle than any other specie, this review will be focused on somatic cell cloning of cattle.